Dysphagia in hospitalized patients: Prevalence, related factors and impact on aspiration pneumonia and mortality. (16th December 2022) - Bosch, Guillermo; Comas, Mercè; Domingo, Laia; Guillen‐Sola, Anna; Duarte, Esther; Castells, Xavier; Sala, Maria
Abstract: Background: Oropharyngeal dysphagia can be highly concerning in hospitalized patients, increasing morbidity and mortality, making its early identification essential. We aimed to characterize dysphagia and its association with aspiration pneumonia and mortality in a tertiary hospital in Barcelona, Spain. Methods: Using data from all hospital discharges during the period 2018–2021, we identified the characteristics of patients with dysphagia and their distribution among hospital departments through the minimum data set, which codifies patients' diagnoses according to the International Classification of Diseases 10th Revision (ICD‐10). We used logistic regression models to assess the association between dysphagia, aspiration pneumonia and mortality. Results: Dysphagia was present in 2.4% of all hospital discharges and was more frequent in older patients and in men. The diagnoses most frequently associated with dysphagia were aspiration pneumonia (48.2%) and stroke (14%). Higher prevalence of dysphagia was found in the acute geriatric unit (10.3%), neurology (7.6%) and internal medicine (7.5%) wards. Dysphagia was associated with aspiration pneumonia, aOR = 8.04 (95%CI, 6.31–10.25), and independently increased the odds of death among hospitalized patients, aOR = 1.43 (95%CI, 1.19–1.73). Conclusions: We conclude that dysphagia is a prevalent and transversal condition, increasing the risk of mortality in all patients, and efforts should be intensified to increase its early detection and correct management. Abstract : Among the 75, 936 patients admitted to two tertiary‐level hospitals in Spain between 2018 and 2021, 2.4% were diagnosed with oropharyngeal dysphagia. The diagnoses most frequently associated with dysphagia were aspiration pneumonia (48.2%) and stroke (14%). Higher prevalence of dysphagia was found in the acute geriatric unit (10.3%), neurology (7.6%) and internal medicine (7.5%) wards. Dysphagia was associated with aspiration pneumonia, aOR = 8.04 (95%CI, 6.31–10.25), and independently increased the odds of death among hospitalized patients, aOR = 1.43 (95%CI, 1.19–1.73).